Tapak Lapan Bees Sialang for Family Economic Resistance - Muhammad Jais; Ria Rizkia Alvi; Said Suhil Achmad; Daffeta Fitrilianda (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2023)
Economic resilience goes hand in hand with family welfare. Family economic resilience can be increased through the Sialang Bee Honey Tapak Lapan system. This study aims to increase family economic resilience through the Sialang Bee Honey Tapak Lapan system which is implemented in Desa Segati, Langgam District, Pelalawan Regency. While the type of research used in this research is qualitative research with descriptive techniques. Data was collected through observation, interviews and documentation. With the data analysis technique used in this study is qualitative data analysis, namely data reduction, data presentation, and drawing conclusions are expected to draw the right conclusions. The sialang honey bee business can be included in tapak eight, namely the business of processing forest products. While the sialang bees are carried out in the forest. Implementation of the bee business is carried out in several stages, namely finding, marking and determining property rights, treating, harvesting, marketing. The Sialang bee Tapak Lapan business can increase family economic resilience. This can be seen from the condition of the families who run the business who have a decent place to live, not living with their parents; sufficient income to meet family needs; school age children, all go to school; can give gifts to his parents, a sign of having excess income.